2022
DOI: 10.1186/s12884-022-04466-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and pregnancy outcomes in early- and late-onset preeclampsia with HELLP syndrome: a 10-year retrospective study from a tertiary hospital and referral center in China

Abstract: Background Early-onset preeclampsia (EO-PE) and late-onset preeclampsia (LO-PE) are different subtypes of preeclampsia. We conducted this study to analyze the similarities and differences in the clinical features and pregnancy outcomes in EO- and LO-PE with HELLP syndrome. Methods This was a retrospective study in a tertiary hospital. Eighty-three parturients with HELLP syndrome were allocated into two groups based on the timing of preeclampsia ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Because of the decrease of placental blood supply and the aggravation of placental villus hypoxia and ischemia, the intake of nutrients and oxygen by the fetus decreases, which had adverse effects on the growth and development of the fetus. And it resulted in adverse outcomes such as FGR, fetal distress, hypoxia asphyxia and even death[ 41 , 42 ]. Lisonkovas et al [ 43 ] analyzed the clinical data of singleton pregnancies in 45,668 women and found that early-onset preeclampsia was associated with a significantly higher risk of adverse birth outcomes than late-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the decrease of placental blood supply and the aggravation of placental villus hypoxia and ischemia, the intake of nutrients and oxygen by the fetus decreases, which had adverse effects on the growth and development of the fetus. And it resulted in adverse outcomes such as FGR, fetal distress, hypoxia asphyxia and even death[ 41 , 42 ]. Lisonkovas et al [ 43 ] analyzed the clinical data of singleton pregnancies in 45,668 women and found that early-onset preeclampsia was associated with a significantly higher risk of adverse birth outcomes than late-onset preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of etiology, EOPE and LOPE have different etiological features. LOPE is more related to maternal factors, while EOPE is more correlated to placental factors 31 . Biomarkers (IRGs) have been identified with remarkable accuracy and rapidity for disease surveillance and treatment with the introduction of large‐scale, public and high‐throughput genomic assays in recent years 32 .…”
Section: Discussionmentioning
confidence: 99%
“…LOPE is more related to maternal factors, while EOPE is more correlated to placental factors. 31 Biomarkers (IRGs) have been identified with remarkable accuracy and rapidity for disease surveillance and treatment with the introduction of large-scale, public and high-throughput genomic assays in recent years. 32 Analyzing related characteristics in EOPE and LOPE may contribute to explore the pathogenesis and treatment of preeclampsia.…”
Section: F I G U R E 5 Legend On Next Pagementioning
confidence: 99%
“…The diagnosis of preeclampsia was based on the criteria proposed by the American College of Obstetricians and Gynecologist Association 15 : the presence of a systolic blood pressure ≥ 140 mmHg or a diastolic blood pressure ≥ 90 mmHg with a 24 h urine protein level ≥0.3 g, a protein/creatinine ratio ≥0.3, or signs of end‐organ dysfunction (central nervous system symptoms, elevation of serum transaminases more than two times the normal value, platelet count < 100 000/mL, serum creatinine >1.1 mg/dL or two times the normal serum creatinine value, pulmonary edema). Preeclampsia occurring at less than 34 weeks of gestation was identified as early‐onset (EO) preeclampsia, whereas preeclampsia that occurred at 34 weeks or later was identified as late‐onset (LO) preeclampsia, irrespective of the gestational week at delivery 16 …”
Section: Methodsmentioning
confidence: 99%
“…Preeclampsia occurring at less than 34 weeks of gestation was identified as early-onset (EO) preeclampsia, whereas preeclampsia that occurred at 34 weeks or later was identified as lateonset (LO) preeclampsia, irrespective of the gestational week at delivery. 16 Severe preeclampsia (SPE) features include the following: (1) a systolic blood pressure of 160 mmHg or more or a diastolic blood pressure of 110 mmHg or more on two occasions at least 4 h apart (unless antihypertensive therapy is initiated before this time); ( 2) thrombocytopenia (a platelet count less than 100 000 Â 10 9 /L); (3) impaired liver function as indicated by abnormally elevated blood concentrations of liver enzymes (to twice the upper limit of the normal concentration) and severe persistent right upper quadrant or epigastric pain that is unresponsive to medication and not accounted for by an alternative diagnosis; (4) renal insufficiency (a serum creatinine concentration more than 1.1 mg/dL or a doubled serum creatinine concentration in the absence of other renal diseases);…”
Section: Methodsmentioning
confidence: 99%